Analysis of the relationship between body image, physical activity, and nutritional status in Poltekkes Kemenkes Bengkulu students - Hanipa Yuliana; Betty Yosephin Simanjuntak; Jumiyati Jumiyati (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Adolescence is a vulnerable period for malnutrition, whether overnutrition or undernutrition. Factors related to nutritional status included physical activity and body image. This study aimed to analyze the relationship between body image, physical activity, and nutritional status among Poltekkes Kemenkes Bengkulu students. The research design used an analytical observational approach with a cross-sectional method, and the research sample was taken comprehensively using a total sampling technique and consisted of 98 first-year students. The research was conducted at the Nutrition Department of Poltekkes Kemenkes Bengkulu and took place in April 2024. Body image data were collected using the Multidimensional Body-Self Relations Questionnaire Appearance Scale (MBSRQ-AS), physical activity data were collected using the Global Physical Activity Questionnaire (GPAQ), and nutritional status data were collected using the Body Mass Index (BMI) by converting weight and height. Statistical analyses were performed using the chi-square test. The results showed a relationship between body image (p= 0,002), physical activity (p= 0,001), and the nutritional status of students at Poltekkes Kemenkes Bengkulu. In conclusion, these findings indicate that negative body image is associated with abnormal nutritional status, low physical activity can lead to overweight, and excessive physical activity can cause underweight.